(untitled) (Research, Society and Development, 2020)
The study aimed to analyze the epidemiological pattern of COVID-19 between Italy and China. The question that guided the review was: What were the epidemiological factors that led to the expression of COVID-19 between China and Italy? The search for the articles was carried out in April 2020 in the following databases: Scielo, Pubmed, VHL, ScienceDirect and Medline, using the following keywords: Coronavirus infections, epidemiology and risk factors. Studies show notable differences in the mortality rate between Asian and European populations. Three risk factors for worsening due to COVID-19 were listed: male gender, advanced age (older than 60 years) and the presence of comorbidities, especially chronic ones. Such factors were predominant mainly in Italy, compared to China. Hypertension, diabetes, cardiovascular diseases and cerebrovascular diseases are considered to be significant risk factors for COVID-19 and its worsening. Studies show that for both countries, being elderly and male increases the risk of contracting the disease in its most severe form. Further, more in-depth studies are needed regarding the harmful effects of chronic diseases as risk factors for COVID-19 infection.